2022
DOI: 10.1111/1759-7714.14344
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of heterotopic pancreas as middle esophagus adenocarcinoma—A rare case report and comprehensive literature review

Abstract: Heterotopic pancreas is a rare congenital abnormality that occurs during the growth and development process. It can be found in any part of the digestive tract, but the most common sites are the stomach, duodenum, and jejunum. Malignant transformation especially in the esophagus is rare. Here, we aim to report an unusual case of mid-esophageal adenocarcinoma that originated from a heterotopic pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Lesion size may range from a few millimeters to as large as 4 cm. 13,14 Our patient had a very small focus of ectopic pancreatic tissue that could not be detected on radiologic examination. Even gross examination of the specimen did not reveal any definite subepithelial lesion, although the thickness of the gallbladder wall was mildly increased.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Lesion size may range from a few millimeters to as large as 4 cm. 13,14 Our patient had a very small focus of ectopic pancreatic tissue that could not be detected on radiologic examination. Even gross examination of the specimen did not reveal any definite subepithelial lesion, although the thickness of the gallbladder wall was mildly increased.…”
Section: Discussionmentioning
confidence: 86%
“…Ectopic pancreatic tissue may undergo metaplasia or even neoplastic transformation that affects the normal pancreas. 14 However, because of the low rate of malignant transformation, ranging from 0.7% to 1.8%, current recommendations do not support routine biopsy or followup screening for incidental ectopic pancreatic tissue. 14 In 2017, Vitiello et al reported that an effective treatment for symptomatic ectopic pancreatic lesions >3 cm is endoscopic mucosal resection and endoscopic submucosal dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of heterotopic pancreas ranged from 3.4% to 4.7%, which was considered as a rare congenital abnormality during the growth and development process. Nevertheless, it has been recently reported that few unusual cases of heterotopic pancreas contributed to malignant transformations [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following three criteria are recommended for diagnosing cancer originating from ectopic pancreatic tissues: (1) the tumor is present within or close to the ectopic pancreatic tissue, (2) direct transition is observed between the pancreatic structures and carcinoma, and (3) nonneoplastic pancreatic tissue must comprise at least fully developed acini and ductal structures 20 . A previous 8 study reported adenocarcinoma arising from ectopic pancreatic tissue in the esophagus and non-neoplastic ectopic pancreatic tissue in the surrounding area 21 . As our case occurred in the midline of the thoracic cavity, we suspected that it may have originated from ectopic pancreatic tissue in the esophagus.…”
Section: Textmentioning
confidence: 99%